An assessment of nutrition information on front of pack labels and healthiness of foods in the United Kingdom retail market - D. A. Ogundijo; A. A. Tas; B. A. Onarinde (BMC, 2021)
Abstract Background Front of pack nutrition labelling is part of United Kingdom government's programme of activities aiming to tackle diet-related diseases. There are several front of pack labelling formats available and they differ in the information they deliver. This study assessed the frequency of usage of front of pack food labelling systems on food products in the United Kingdom grocery market. It also measured the healthiness of some foods in the online market by categorising them according to their nutrient contents. Methods Five hundred food products in five categories [(1) cereals and cereal products, (2) dairy products, (3) beverages, (4) packaged meats and meat products, and (5) pre-packaged fruits and vegetables] from three main United Kingdom retail websites were investigated. A simple random sampling method was used for product selection according to the categories on the retailers' websites. The healthiness of foods was also assessed by categorising them into 'healthier', 'moderately healthy' and 'least healthy' based on fat, saturated fat, salt and sugar contents. Results The total number of label types assessed comprises 19.6% of Guideline Daily Amounts or Reference Intakes and 43.8% had a combination of Traffic Light and Reference Intakes (hybrid label). Slightly over a quarter (27.4%) of products included nutritional information in a grid or table, 3.4% of the foods had two of any of the following: Health Logo, Reference Intakes and Traffic Light labels, and 5.8% did not have any Reference Intakes, Traffic Light, Health Logo or Hybrid label. Most of the foods assessed were manufactured in the United Kingdom with only 30.8% imported from 32 countries across four continents. Conclusions Traffic Light and Guideline Daily Amounts were the most used front of pack labelling formats on the assessed food product. A higher number of assessed products belonged to the "moderately healthy" and "healthier" categories than the "least healthy". The imported foods that were found in the United Kingdom retail market showed that food choices could be made from the diverse food types.